Nuclear volume differences between balanced and unbalanced spermatozoa in chromosomal translocation carriers. Issue 3 (March 2015) - Rouen, Alexandre; Lavillaureix, Alinoë; Hyon, Capucine; Heide, Solveig; Clède, Sylvain; Balet, Richard; Kott, Esther; Cassuto, Nino Guy; Siffroi, Jean-Pierre
Abstract While chromosomal translocations are usually associated with a normal phenotype, they can still cause male infertility as well as recurrent miscarriages and fetal malformations related to their transmission in an unbalanced state. The distinction between balanced and unbalanced spermatozoa on morphological criteria is still unfeasible. However, we previously showed that: i) spermatozoa with an unbalanced content have a higher rate of DNA fragmentation; and ii) that density gradient centrifugation partially separates balanced from unbalanced sperm cells. We hypothesized that a chromosomal imbalance could alter the fine spermatic nuclear architecture and consequently the condensation of DNA, thus modifying normal sperm density. Spermatic nuclear volumes in four translocation carriers were analyzed using confocal microscopy. Secondarily, FISH analysis was used to establish the segregation mode of each spermatozoon. We found the average spermatic nuclei size to be higher among unbalanced spermatozoa in all patients but one. All the unbalanced modes were associated with larger nuclei in two patients, while this was the case for the 3:1 mode only in the other two, suggesting an abnormal condensation. This could be the first step in elaborating a procedure to completely eliminate unbalanced spermatozoa from semen prior to in vitro fertilization.